Respuesta :

Answer:

The answer is 9996

Step-by-step explanation:

Using the identity (x+a)(x+b) = x  ^2  +(a+b)x+ab

Writing 102 as 100+2 and 98 as 100−2

Hence (100+2)(100−2) = 100  ^2  +[2+(−2)]100+(2)(−2)

= 10000+(0)100−4

= 9996

The answer is 9996

Answer:

9996

Step-by-step explanation:

by using suitable identities ;

  • (98) × (102)
  • (100 - 2) × (100 + 2)
  • 10000 - 4
  • 9996

identity used here is :

[tex](a + b) \times (a - b) = (a {}^{2} - b {}^{2} )[/tex]

..........................

ACCESS MORE